Исследование вынужденных колебаний двух лопаток с учетом контакта в межбандажном соединении - Демуз, Я. Д.; Жовдак, В. А.; Степаненко, А. С. (НТУ "ХПИ", 2006)
In the given work the task about forced vibrations of blades is considered in view of contact interaction in blade-to-blade connection. The algorithm of calculation of non-linear vibrations designed in view of contact interaction.
Keywords: лопаточный аппарат; истинный вектор нагрузок; бандажная полка; квазигармонический процесс